2008
DOI: 10.1063/1.2907851
|View full text |Cite
|
Sign up to set email alerts
|

Recrystallization of epitaxial GaN under indentation

Abstract: We report recrystallization of epitaxial (epi-) GaN(0001) film under indentation.Hardness value is measured ~10 GPa, using a Berkovich indenter. 'Pop-in' burst in the loading line indicates nucleation of dislocations setting in plastic motion of lattice atoms under stress field for the recrystallization process. Micro-Raman studies are used to identify the recrystallization process. Raman area mapping indicates the crystallized region. Phonon mode corresponding to E 2 (high) ~570 cm -1 in the as-grown epi-GaN … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 16 publications
1
15
0
Order By: Relevance
“…A 1 (TO) be the starting of A 1 symmetry phonon modes and this frequency corresponds to the quasi-confined modes in isolated nanowire model which are the continuation of SO modes for frequencies below A 1 (TO). TO modes will appear when the orientations have different crystalline planes [28]. TO vibration modes are exhibited when the q vector (propagation direction) travels in between the c-and a-planes.…”
Section: Optical Propertiesmentioning
confidence: 99%
“…A 1 (TO) be the starting of A 1 symmetry phonon modes and this frequency corresponds to the quasi-confined modes in isolated nanowire model which are the continuation of SO modes for frequencies below A 1 (TO). TO modes will appear when the orientations have different crystalline planes [28]. TO vibration modes are exhibited when the q vector (propagation direction) travels in between the c-and a-planes.…”
Section: Optical Propertiesmentioning
confidence: 99%
“…These high stresses are reported for pressure-induced phase transformations to denser crystalline (c-) and amorphous forms in monovalently [1 -3] and covalently bonded compound [4,5] semiconductors along with plastic deformation, leading to recrystallization by dislocation activity in ionic-bonded compound semiconductors. [6] Study of materials under pressure is always of immense interest both for electronic and mechanical properties. In addition, the study of transformation to the high-pressure phase has technological importance for having control in the precision micromachining process steps using enhancement of ductility in these systems.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism responsible for the 'pop-in' bursts appears to be associated with the nucleation and movement of dislocation sources. [14,15] A hardness value of ∼10 GPa is achieved in our indentation study, [2] and the value is comparable to the bulk value of GaN. [16] It is also observed that the hardness of the GaN film is also sensitive to the loading rate (strain rate), as shown in Fig 3(a).…”
Section: Nucleation and Dynamics Of Defects Under Indentation Stress mentioning
confidence: 54%
“…A detailed description of compliance curve along with 'pop-in' bursts in the loading line is reported in our earlier studies, [2] and also shown in Fig. S1 (Supporting Information) for high and low loads.…”
Section: Nucleation and Dynamics Of Defects Under Indentation Stress mentioning
confidence: 99%
See 1 more Smart Citation